2010
DOI: 10.1007/s10877-010-9260-2
|View full text |Cite
|
Sign up to set email alerts
|

Effective hypertensive treatment using data mining in Saudi Arabia

Abstract: In the present investigation, the data sets of NCD (Non Communicable Diseases) risk factors, a standard report of Saudi Arabia 2005, in collaboration with WHO (World Health Organisation) were employed. The Oracle Data Miner (ODM) tool was used for the analysis and prediction of data. The data sets for different age groups in case of blood pressure treatment for hypertension for male using different modes had been studied. The age group was in between of 15 and 64 years. Data mining had been an appropriate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 8 publications
1
7
0
1
Order By: Relevance
“…E-health in Saudi Arabia is growing, as many organizational and individual initiatives have implemented e-health applications. Many studies are available in the literature about e-health in Saudi Arabia [ 10 – 34 ], however, data is limited to a few organizations and does not necessarily reflect the current and potential use of e-health for health care organizations in the country [ 35 ]. A descriptive analysis of the status of e-health in Saudi Arabia highlighted the national e-health initiatives such as the establishment of a new Master of Health Informatics degree program at King Saud bin-Abdulaziz University for Health Sciences (KSAU-HS) as an initiative to educate specialized professionals [ 11 ], with an e-health course to foster future professional development in this field in the country [ 15 ] and the role of the Saudi Association for Health Informatics (SAHI) in enhancing coordination among health information professionals [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…E-health in Saudi Arabia is growing, as many organizational and individual initiatives have implemented e-health applications. Many studies are available in the literature about e-health in Saudi Arabia [ 10 – 34 ], however, data is limited to a few organizations and does not necessarily reflect the current and potential use of e-health for health care organizations in the country [ 35 ]. A descriptive analysis of the status of e-health in Saudi Arabia highlighted the national e-health initiatives such as the establishment of a new Master of Health Informatics degree program at King Saud bin-Abdulaziz University for Health Sciences (KSAU-HS) as an initiative to educate specialized professionals [ 11 ], with an e-health course to foster future professional development in this field in the country [ 15 ] and the role of the Saudi Association for Health Informatics (SAHI) in enhancing coordination among health information professionals [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, applications of data mining have been widely seen on the prediction of the best mode for the intervention of chronic diseases such as hypertension and diabetes. For this, the Oracle Data Miner (ODM) tool has been prominently used in order to explore the meaningful patterns for predicting the effective mode of intervention [18][19][20][21]. Few of the related works have been discussed here.…”
Section: Applications Of Data Mining On Chronic Diseases Analysis Andmentioning
confidence: 99%
“…Different risk factors have been analyzed for hypertension interventions by Naïve Bayesian classifier and found quitting smoking is more effective [20]. A research was carried out to predict which type of treatment is more effective in hypertension using ODM and found that quitting smoking is an effective mode to prevent hypertension [21].…”
Section: Applications Of Data Mining On Chronic Diseases Analysis Andmentioning
confidence: 99%
“…Diğer bir çalışmada, 15-64 yaş aralığındaki erkeklerin, belirlenen 5 tedavi çeşidinin hangi yaş aralığında daha etkin sonuç verdiğinin analizi için veri madenciliği algoritmaları kullanılmıştır (Almazyad, Ahamad, Siddiqui, & Almazyad, 2010).…”
Section: Introductionunclassified